Pelatihan Desain E-Modul Berbasis Aplikasi Heyzine Flipbook bagi Guru SMK YAPIM Pekanbaru - Satriani, Estika; Pryanti, Destry (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase the creativity of YAPIM Pekanbaru Vocational School teachers in compiling interesting and innovative E-modules based on the Heyzine Flipbook application to create quality learning. The method for implementing this service was training with stages including planning, presentation of material, practice, mentoring and evaluation. This training used a questionnaire instrument given to participants as an evaluation instrument and analyzed descriptively. The result of this service activity showed that teachers had Heyzine Flipbook accounts so they could design teaching materials for all subjects freely. Apart from that, teachers could use e-modules that had been designed for use in the classroom learning process. Moreover, teachers felt more challenged to create more varied teaching materials by using the Heyzine Flipbook feature. Apart from developing technological knowledge in learning, the design of e-module teaching materials could also support maximum learning implementation.